Conservative Treatment of Urinary Incontinence after Radical Prostatectomy - Bates H. Pearce, Douglas P. Alec, Arthur D. Walter (Open Journal of Physicians and Surgeons, 2024)
Nonsurgical approaches that aim at improving the quality of life of the patient are emphasized in the conservative treatment of urinary incontinence after RP. Often this condition arises because of surgical removal of the prostate tissues, which can interfere with urinary control. Some of the conservative approaches include interventions such as bladder training, pelvic floor muscle training as well as change of lifestyle such as bout of obesity and diet changes. PFMT which incorporates Kegel exercises in most occasions helps support and control the bladder by strengthening the pelvic muscles. Bladder training enables patients to extend the time between two voids and helps reduce bladder urgency and frequency. Also, strategies controlling the dysfunctional bladder, such as regimens of prompt package, help tackle the symptoms well. Moreover, electrical stimulation techniques and biofeedback procedures are added to the pelvic muscle training to stimulate the muscles. Such procedures are flexible, since they can be tailored to the particular demands of any patient, hence making them suitable for almost all patients. These reports contribute to simpler incontinence management, maintaining patient satisfaction and reducing the severity of incontinence. While there are surgical options, conservative treatment is an option that is commonly recommended at first as it may relieve symptoms without the need for an invasive procedure